Role of type-specific herpes simplex virus-1 and 2 serology as a diagnostic modality in patients with clinically suspected genital herpes: A comparative study in Indian population from a tertiary care hospital - Vrushali Patwardhan; Preena Bhalla (Wolters Kluwer Medknow Publications, 2016)
Introduction: Type-specific serology (TSS) test for herpes simplex virus (HSV) have been used as a research tool in seroepidemiological studies for some years. However, TSS as a diagnostic modality for diagnosis of current episode of genital herpes is not well documented. Aims and Objectives: To measure the seroprevalence of type-specific HSV Type 1 (HSV-1) and Type 2 (HSV-2) IgG antibodies in cases provisionally diagnosed as primary and recurrent genital herpes and to evaluate the role of TSS as a diagnostic modality for diagnosis of genital herpes versus polymerase chain reaction (PCR). Materials and Methods: A cross-sectional study was performed over a period of 10 months in which 44 adult patients with clinically suspected genital herpes were recruited. An in-house glycoprotein G gene base PCR was performed directly from the genital lesion specimen for simultaneous detection and typing of HSV. TSS was performed to detect IgG antibody against HSV-1 and 2 in all patients using commercially available kits, and the results were compared. Results: Seroprevalence of HSV-1 IgG was 43% among primary and 65% among recurrent genital herpes cases (P = 0.22). Whereas that of HSV-2 IgG was found to be 14% and 83% in respective patient group (P = 0.0001). When compared to PCR results HSV-1 IgG detection in both primary and recurrent genital herpes diagnosis had poor specificity, positive predictive value, and sensitivity. Whereas, HSV-2 serology had a sensitivity of 13.33% and 73.33% in primary and recurrent genital herpes and specificity of 83.33% and 85.71%, respectively. Conclusion: HSV-2 IgG detection helps in strengthening the diagnosis of recurrent HSV-2 disease, whereas the absence of HSV-2 IgG antibody helps in excluding genital herpes as a likely cause of recurrent genital ulceration. However, detection of HSV-1 IgG antibody may not be useful for diagnosis in patients of genital ulcer disease.